Factors Influencing Going Concern Audit Opinion (Empirical Study of Manufacturing Companies Listed on the Indonesian Stock Exchange) - Sintia, Dea; Indriani, Poppy (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
This research aims to determine the influence of profitability, leverage, company growth, previous year’s audit opinion, and company size on ongoing concerned audit opinions in manufacturing companies listed on the Indonesia Stock Exchange. A going concern audit opinion is given to a company that has financial problems but is considered capable of continuing its business within a reasonable period of time. This research uses secondary data from audited financial reports, which can be accessed via the Indonesia Stock Exchange website, namely www.idx.co.id.The population in this study was 136 manufacturing companies, and the sample used was 50 companies. The sampling method is purposive sampling with data analysis techniques using logistic regression. The results of this research show that the previous year’s audit opinion influences the going concern audit opinion Meanwhile, profitability, leverage, company growth and company size do not affect going concern audit opinion